Representation of Character in Edgar Allan Poe’s Works and Biographical Dissimilarities in Scott Cooper’s The Pale Blue Eye (2022) Film - Ellyana Ellyana; Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
This study is aim to analyze: (1) the representation of characters in Edgar Allan Poe’s works in The Pale Blue Eye (2022) film, and (2) the similarities and dissimilarities between the biography and the character of Edgar Allan Poe in The Pale Blue Eye (2022) film. The study uses a descriptive qualitative method to analyze the film entitled The Pale Blue Eye directed by Scott Cooper as the objective research. The collecting data of the research method includes watching, reading, identifying, classifying, and selecting. The researcher analyzes the data by using Linda Hutcheon’s theory of Adaptation and Transformation. It is done through some steps as displaying, explaining, and interpreting. The result of this research shows that: (1) the representation of some of Edgar Allan Poe’s works in The Pale Blue Eye includes “The Premature Burial,” “The Tell-Tale Heart,” “The Pit and The Pendulum,” “Lenore,” “The Gold-Bug,” and “Landor’s Cottage.” These works serve as crucial elements in establishing the main characters, including Augustus Landor, Edgar Allan Poe, and Lea Marquis, contributing to the portrayal of their personalities, motivations, and relationships; (2) there are similarities between the character depicted in the film and the real life Poe, such as an interest in poetry, French language skills, training at the West Point Military Academy, and alcohol preference and there are also differences, such as involvement in murder investigation, military discipline, financial problems, family relationships, and literary recognition.